Interpretive theory of mind and empathic prosocial moral reasoning. (13th August 2020) - Harari, Yifat; Weinstock, Michael
Abstract : Theory of mind (ToM) is seen as fundamental in development of social understanding. The study proposes that interpretive theory of mind (iToM), which follows ToM attainment, underlies important shifts towards mature social understanding. With ToM found to predict the needs orientation in prosocial moral reasoning (PMR), we hypothesized that iToM, unlike ToM, would account for PMR orientations requiring empathic reasoning. Those with iToM recognize the role of subjective processes, such as interpretation, in knowing. They can invoke others' subjective processes, not just their physical perspectives, in explaining others' decisions. A study with 225 7‐ to 11‐year‐old children ( M age  = 9.04, SD  = 0.91) found that iToM, but not ToM, predicted empathic and internalized values PMR orientations when controlling for age, emotion understanding and inhibitory control. These findings show that iToM attainment plays a unique role in developing social understanding such as reflected in empathic reasoning‐based PMR orientations.